Russian industry in the context of digital transformation - I. N. Ivanov; L. V. Orlova; G. M. Sundukova (Вестник университета, 2022)
The directions of industrial policy in the Russian Federation in the context of digital transformation were considered in the article. The problems of Russian industry and the reasons for their occurrence were analysed. The preference for the so-called “horizontal” model based not on tough measures to support industries and companies, but on the creation of a comfortable environment for the functioning of all participants in the industrial market was emphasised. The requirement for the new development strategy formation in the industry and innovative business models implementation of this strategy has been justified. The basis of these models should be a technology platform based on continuous innovations performed by all participants in the network. A promising cooperation form between these participants is industry clustering. The positive experience of the innovative industrial clusters formation has been presented, especially successful in conjunction with modern information and communication technologies. Effective ways of forming and developing these clusters have been shown, especially promising with the small and medium businesses inclusion in technological industrial chains.